Evaluation of burst release and sustained release of pioglitazone-loaded fibrous mats on diabetic wound healing: an in vitro and in vivo comparison study - AKAKIN, DİLEK; KABASAKAL, LEVENT; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (ROYAL SOC, 2020)
In order to provide more effective treatment strategies for the rapid healing of diabetic wounds, novel therapeutic approaches need to be developed. The therapeutic potential of peroxisome proliferator-activated receptor-gamma (PPAR-gamma) agonist pioglitazone hydrochloride (PHR) in two different release kinetic scenarios, burst release and sustained release, was investigated and compared with in vitro and in vivo tests as potential wound healing dressings. PHR-loaded fibrous mats were successfully fabricated using polyvinyl-pyrrolidone and polycaprolactone by scalable pressurized gyration. The results indicated that PHR-loaded fibrous mats expedited diabetic wound healing in type-1 diabetic rats and did not show any cytotoxic effect on NIH/3T3 (mouse embryo fibroblast) cells, albeit with different release kinetics and efficacies. The wound healing effects of fibrous mats are presented with histological and biochemical evaluations. PHR-loaded fibrous mats improved neutrophil infiltration, oedema, and inflammation and increased epidermal regeneration and fibroblast proliferation, but the formation of hair follicles and completely improved oedema were observed only in the sustained release form. Thus, topical administration of PPAR-gamma agonist in sustained release form has high potential for the treatment of diabetic wounds in inflammatory and proliferative phases of healing with high bioavailability and fewer systemic side effects.
Keywords: burst release; sustained release; drug delivery; fibres; diabetic wound healing; pioglitazone; PROLIFERATOR-ACTIVATED RECEPTOR; GAMMA AGONIST; PPAR; DELIVERY; FIBROBLASTS